2017
DOI: 10.1038/s41522-017-0020-7
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of donor microbe species that colonize and persist long term in the recipient after fecal transplant for recurrent Clostridium difficile

Abstract: Fecal microbiota transplantation has been shown to be an effective treatment for patients with recurrent C. difficile colitis. Although fecal microbiota transplantation helps to re-establish a normal gut function in patients, the extent of the repopulation of the recipient microbial community varies. To further understand this variation, it is important to determine the fate of donor microbes in the patients following fecal microbiota transplantation. We have developed a new method that utilizes the unique sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(115 citation statements)
references
References 22 publications
3
109
1
2
Order By: Relevance
“…For the WSS analysis, high-quality processed reads were aligned to the 93 microbial reference sequences [9], which were common and dominant in stool samples collected from healthy European and North American donors [6,9] using the Burrows-Wheeler aligner tool BWA-MEM (v. 0.7.13) with the '-M' option [25]. Mapped reads were then filtered to exclude reads mapped on multiple locations or a low percentage match (less than 90%) using 'mgSNP_sam-filter.py' implemented in the WSS.…”
Section: Strain-tracking Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the WSS analysis, high-quality processed reads were aligned to the 93 microbial reference sequences [9], which were common and dominant in stool samples collected from healthy European and North American donors [6,9] using the Burrows-Wheeler aligner tool BWA-MEM (v. 0.7.13) with the '-M' option [25]. Mapped reads were then filtered to exclude reads mapped on multiple locations or a low percentage match (less than 90%) using 'mgSNP_sam-filter.py' implemented in the WSS.…”
Section: Strain-tracking Analysesmentioning
confidence: 99%
“…Also, a low coverage window with more than 50% of the bases having a read depth less than 5 were ignored when comparing the SNV similarity between sample pairs. All codes implemented in the WSS were deposited and are available at https://github.com/hkoo87/mgSNP_2 [9].…”
Section: Strain-tracking Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the recipient microbiota composition post‐FMT is different from pretransplant, the degree of similarity to the donor microbiota after FMT is different among patients . It has been shown that donor bacteria can persist in recipients up to 2 years post‐FMT . In a recent study of FMT for CDI in immunocompromised stem cell recipients, a shotgun metagenomic approach to examine both short‐ and long‐term bacterial engraftment demonstrated that, although concordance was observed between microbiota composition of the donor and recipient in the short‐term, concordance was reduced after 1 year, suggesting that FMT cannot indefinitely supersede environmental or host factors in shaping future bacterial composition …”
Section: Microbial Implications Of Microbiota Replacement Therapiesmentioning
confidence: 99%
“…To understand the effects of FMT induced microbiome reconstruction, it becomes important to understand the success of bacterial engraftment following fecal transplantation. Several studies have shown the success of utilizing single-nucleotide variants (SNV) based methods for tracking the dynamics between donor and recipient microbiomes following FMT [20,21,22]. The study by Li et al on metabolic syndrome patients using SNV in metagenomes enabled the quantification of the extent of donor microbiota colonization after FMT, revealing extensive coexistence of donor and recipient strains, persisting 3 months after treatment.…”
Section: Introductionmentioning
confidence: 99%